A new approach of applying cryogenic coolant in turning AISI 304 stainless steel - Khan, Ahsan Ali; Ali, Mohammad Yeakub; Haque, Md. Mohafizul (Universiti Malaya, 2010)
In the present study a special device has been designed to apply liquid nitrogen coolant during turning of AISI 304 stainless steel. The base of the device is a magnet and it can be fixed at any suitable position on the tool or tool post. A long flexible and adjustable copper nozzle is used to apply liquid nitrogen at any angle or from any position. Experiments with three positions of the copper nozzle were performed. The results of the investigations showed that the most effective way to apply liquid nitrogen directly to the machining zone without any interference by the chips. Tool life increased four times compared to dry machining under this condition. The next effective way was to apply liquid nitrogen along the principal cutting edge. It was found that application of liquid nitrogen coolant did not improve job surface finish, but all the three positions of the copper nozzle demonstrated almost similar effectiveness.